Avaliação do estresse oxidativo em gestantes com diabetes mellitus pré-existente e gestacional - Paula, Hellen Lopes de (2019)
During the normal gestational period, there is an elevation of oxidative metabolism due to the high demand for oxygen required by the mother, fetus and placenta. In pregnant women with additional pathologies, such as Diabetes Mellitus (DM), these circumstances may be even greater. DM is a metabolic disorder of diverse origin, characterized by hyperglycemia and changes in the metabolism of carbohydrates, proteins and fats, which are generated by the defect in the action and/or secretion of insulin. In pregnancy this pathology may be present in two ways: prior to pregnancy and developed in the gestational period, thus generated at different times in the body. Oxidative stress is said to be the state where the loss of balance between oxidants and antioxidants in the body occurs, primarily as a result of increased production of reactive oxygen species (ROS), and plays an important role in the pathogenesis of many diseases, including diabetes and complications. In this context, the enzyme delta- aminolevulinate-dehydratase (δ-ALA-D) is also inserted, since this enzyme may be inhibited in pro-oxidative situations, causing a decrease in the biosynthesis of compounds, as in the case of the heme group, and its substrate 5-aminolevulinic acid (ALA), which directly contributes to the elevation of this oxidative state by the accumulation of ROS. Considering the influence of oxidative stress on pregnancy and on DM, this study aimed to evaluate, in a comparative way, the oxidative and antioxidative profile, as well as the δ-ALA-D enzyme activity, in pregnant women with previous type 2 diabetes gestation (DM2), Gestational Diabetes Mellitus (DMG) and control group (healthy pregnant women). Oxidative stress parameters were analyzed by quantification of thiobarbituric acid reactive species (TBARS), protein thiol groups (P-SH) and non-protein (NP-SH) groups, vitamin C levels, and determination of enzyme activity catalase and δ-ALA-D, in the different groups of pregnant women. The levels of TBARS were higher, whereas NP-SH and vitamin C were decreased in pregnant women with DM, with no significant difference between the two groups. The P-SH levels were significantly reduced in pregnant women with DMG, and the activity of the enzyme catalase in the DM2 group. The activity of the δ-ALA-D enzyme was significantly reduced in samples from pregnant women with GDM, whereas in the group with DM2 prior to gestation, it was similar to the control. Thus, it is confirmed that oxidative stress is higher in pregnant women with DM, as well as diminished antioxidant defenses, and although both types of diabetes may be present during pregnancy, and are generated by carbohydrate intolerance, they are differentiated events and, therefore, produce different effects in the maternal organism.